Pathways of intracellular protein degradation in cultured muscle cells - Bates, Pamela Joy (Division of Medical Biochemistry and Structural Biology, 2018)
To investigate mechanisms responsible for the turnover of endogenous muscle protein, lysosomotropic proteinase inhibitors have been employed to elucidate the relative contributions of lysosomal and non-lysosomal degradation pathways functioning under varying nutritional states and for different classes of intracellular proteins. Proteolysis in cultured bovine aortic smooth muscle cells was measured as the percentage of ³H-phenylalanine released per hour from pre-labelled cellular proteins. To reduce background radioactivity, the intracellular ³H-phenylalanine pool was depleted by serial extraction at 37°C, effecting equilibration between the intracellular pool and the phenylalanine-free medium. Reutilization of labelled amino acids during subsequent incubation periods was minimized by the presence of excess non-labelled phenylalanine in the medium. ³H-phenylalanine was released at a constant rate of 1,5 % per hour for at least 4 h, from cells pre-labelled for 16 h ('long-lived' proteins). Leupeptin, an inhibitor of thiol proteinases including cathepsin 8, inhibited degradation by 12 %, whereas the general lysosomal inhibitors chloroquine and NH₄Cl inhibited degradation by 30 %, presumably the contribution by the lysosomal pathway. In the case of 'short-lived' proteins (pre-labelled for 1 hour), the initial degradation rate was 6,5% per hour, which rapidly declined, reaching the basal rate of 1,5 % after 4 h. Chloroquine and NH₄Cl reduced proteolysis by only 12-15% and leupeptin had no significant inhibition, consistent with the view that the majority of short-lived proteins a degraded by non-lysosomal pathways. Proteolysis rates of 'abnormal' proteins containing the arginine-analogue, canavanine, were found to be significantly elevated (80 %) over controls. Leupeptin had no significant inhibition, and chloroquine and NH₄Cl only reduced degradation by 12-16 %, showing that the rapid removal of 'abnormal' intracellular proteins proceeds mainly via extra-lysosomal mechanisms. Incubation of the cells under nutritional step-down conditions, increased the average degradation rate of long-lived proteins to 3% per hour, and chloroquine and NH₄Cl inhibited degradation by 55-60 %, indicating that the accelerated proteolytic condition is due to increased activity of the lysosomes. Nutritional deprivation did not increase the rate of degradation of short-lived proteins. The results were clarified by the parallel use of the well-characterized LDL degradation system in this cell type, known to occur almost exclusively via lysosomes. This allowed the effectiveness of lysosomotropic inhibitors to be tested. Chloroquine inhibited LDL degradation by over 90 % and NH₄Cl inhibited by 80-95 % in all cases. Other proteinase inhibitors such as chymostatin, pepstatin and the chloromethyl ketones were also tested, and of these chymostatin seemed to be the most valuable because of its additivity to the effect of chloroquine, indicating its selective inhibition of non-lysosomal degradative mechanisms. Incubations of smooth muscle cells under anoxic conditions or with metabolic inhibitors such as fluoride, azide and cyanide, resulted in an inhibition of protein degradation which was greater than, and partially additive to, the effect of chloroquine, i.e. both lysosomal and non-lysosomal degradation pathways have some energy-dependence. The degradation of long-lived proteins appeared to be more sensitive to temperature than that of short-lived proteins, further indicating the activity of distinct proteolytic mechanisms for these two classes of intracellular proteins. Preliminary studies have indicated a role for Ca⁺⁺ in the regulation of proteolysis, since degradation rates were increased by elevated levels of Ca⁺⁺ in the extracellular medium. Inhibition of this increased proteolysis by leupeptin has indicated a role for a thiol proteinase, possibly Ca⁺⁺-activated neutral proteinase. In similar studies with cultured L8 skeletal muscle cells, an average proteolysis rate of 1,2 % per hour was found, which was increased by 50 % under nutritional step-down conditions. Once again, the lysosomal pathway was found to account for only about one-third of basal protein degradation but fully accounted for the increased proteolysis under nutrient deprivation. The degradation characteristics of intracellular smooth and skeletal muscle cell proteins was examined using double isotope labelling. It was found that large molecular weight proteins and glycoproteins tended to be degraded more rapidly than small proteins and non-glycoproteins. In smooth muscle cells, these correlations were markedly reduced or absent under the accelerated proteolysis associated with nutrient deprivation, possibly confirming the increased activity of the non-selective autophagic lysosomal pathway under these conditions. A similar loss of correlations was not so clearly seen for skeletal muscle cell proteins.